Effects of skin abrasion in immersion challenge with Vibrio harveyi in Asian seabass Lates calcarifer fingerlings - Chin, Yong Kit; Md Yasin, Ina‐Salwany; M, Zamri-Saad; Al-saari, Nurhidayu (2020)
Skin abrasions often occur in farmed fish following handling by labourers, injury by farm facilities, cannibalism and ectoparasites. Vibrio spp. are opportunistic pathogens that can invade host fish through damaged tissues and cause outbreaks of vibriosis. This study describes the effect of skin abrasions on the infectivity of V. harveyi using Asian seabass Lates calcarifer (Bloch, 1790) fingerlings as a case example and compares bacterial load and fish survival following immersion challenge with different doses. In total, 315 fish (6.67 ± 1.8 g) were divided into 3 treatments: skin abrasion followed by immersion infection, immersion infection only and an uninfected, uninjured control. Fish in the infection treatments were divided into 3 subgroups and exposed in triplicate to a 7 d immersion challenge with 106, 107 and 108 CFU ml−1 of live V. harveyi. No mortalities were observed in the control and immersion infection groups. However, fish in the skin abrasion treatment group that were infected with 108 CFU ml−1 of live V. harveyi showed signs of progressing disease throughout the experiment, which resulted in mortalities. Significantly higher bacterial loads (p < 0.05) were recorded in the intestine, liver and gills of the fish in this group. Fish in the skin abrasion treatment that were exposed to 107 and 108 CFU ml−1 of V. harveyi showed 100% mortality by Days 5 and 4, respectively. These findings confirm that skin injuries increase the susceptibility of seabass fingerlings to V. harveyi infection.